Pediatric Buried Bumper Syndrome: Diagnostic Validity of Transabdominal Ultrasound and Artificial Intelligence - Aguilar, Caroline; Regensburger, Adrian; Knieling, Ferdinand; Wagner, Alexandra; Siebenlist, Gregor; Wölfle, Joachim; Koehler, Henrik; Hörning, André; Jüngert, Jörg M. (Ultraschall in der Medizin, 2021)
Zusammenfassung
CRIS-Team WoS Importer:2021-06-04